Pengembangan E-LKPD Berbasis Liveworksheet Pada Materi Mengenal Bangun Datar Kelas II SD - Ayuna Asri Nurrohmah; Asfi Alfian Nurfaizah; Hani Binti Rishadi; Putri Zudhah Ferryka (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This wThis study aims to develop and describe the use of Liveworksheets-based E-LKPD with a Deep Learning and TPACK approach in teaching flat shapes to second-grade elementary school students. The background of this study is based on the demands of 21st-century education, which emphasizes the importance of critical, creative, collaborative, and communicative thinking skills, as well as the use of technology in learning. The research method used was descriptive qualitative with data collection techniques in the form of observation, tests, and documentation. The data were analyzed through the interpretation of learning outcomes and student engagement during the learning process using Liveworksheets E-LKPD. The results showed that the use of interactive Liveworksheets-based E-LKPD was able to improve students' understanding of plane figure concepts, learning motivation, and active engagement. The presentation of interesting material, a variety of interactive activities, and the provision of feedback and automatic assessment provide a fun and meaningful learning experience. Thus, Liveworksheets-based E-LKPD using the Deep Learning and TPACK approaches are considered effective as innovative and relevant digital learning media for improving the quality of learning and learning outcomes of second-grade elementary school students.